Theory in Highly Cited Studies of Sexual Minority Parent Families: Variations and Implications. Issue 9 (29th July 2017) - Farr, Rachel H.; Tasker, Fiona; Goldberg, Abbie E.
ABSTRACT: This article includes a systematic review and citation analysis of the literature regarding sexual minority parent families, particularly attending to what theories have been used, and how. We consider the importance of theoretical frameworks for future research and implications for policy, practice, and law related to sexual minority parent families. Our review targets 30 highly cited studies located through Google Scholar (as an interdisciplinary search engine) and published within a specific timeframe (2005–2010). We highlight the dominant theoretical models employed across disciplines studying sexual minority parent families. Although the majority of studies reviewed referred to theoretical models or perspectives, explicit theoretical grounding was frequently lacking. Instead, the empirical work reviewed appeared to have a predominantly applied focus in addressing public debates on sexual minority parent families. We provide recommendations for how theory might be more fully integrated into the social science literature on sexual minority parents and their children.